2016
DOI: 10.3171/2015.10.spine15917
|View full text |Cite
|
Sign up to set email alerts
|

Modeled cost-effectiveness of transforaminal lumbar interbody fusion compared with posterolateral fusion for spondylolisthesis using N2QOD data

Abstract: OBJECTIVE Transforaminal lumbar interbody fusion (TLIF) has become the most commonly used fusion technique for lumbar degenerative disorders. This suggests an expectation of better clinical outcomes with this technique, but this has not been validated consistently. How surgical variables and choice of health utility measures drive the cost-effectiveness of TLIF relative to posterolateral fusion (PSF) has not been established. The authors used health utility values de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 34 publications
1
12
1
Order By: Relevance
“…Overall incidence is 62.5% for L4-L5 and 35% for L5-S1 level. 18 In our study, we also observed 88.76% and 89.6% improvement in VAS scores for back pain, 94.8% and 96.5% increase in VAS for leg pain in PLF and TLIF groups respectively. Higher percentage of improvement was seen in TLIF patients, though the difference between the groups is not statistically significant.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Overall incidence is 62.5% for L4-L5 and 35% for L5-S1 level. 18 In our study, we also observed 88.76% and 89.6% improvement in VAS scores for back pain, 94.8% and 96.5% increase in VAS for leg pain in PLF and TLIF groups respectively. Higher percentage of improvement was seen in TLIF patients, though the difference between the groups is not statistically significant.…”
Section: Discussionsupporting
confidence: 80%
“…16 Etemadifar et al, in their RCT, observe that ODI improved by 53.2 in the PLF group and 56.7 in 13 the TLIF group. Carreon et al, 18 reported that the TLIF group made significantly greater improvements in ODI (21.1 in the PLF group vs. 30.4 in the TLIF group; p=0.001). 17 Ghasemi 2016, in a retrospective cohort study, reported that at 24 months follow-up, TLIF patients had significantly less disability as measured by ODI (p <0.05).…”
Section: Discussionmentioning
confidence: 97%
“…35 In an observational study, Carreon et al also compared the clinical improvement in 101 patients with these techniques and the results suggested that visual analog scale scores for back and leg pains improved by 4.2 and 4.6 respectively for TLIF group and 3.5 and 3.7 for PLF group. 36 TLIF exhibited a significantly higher incidence of adjacent segment disease. Fixing intervertebral cages or grafts can increase stress on adjacent sections by increasing segmental rigidity, subsequently accelerating the degenerative process of adjacent segments after surgery.…”
Section: Discussionmentioning
confidence: 88%
“…The investigators found no significant difference in patient-reported outcomes, complications, reoperation rate, gain in QALYs or cost per QALY. Additionally, Carreon et al retrospectively compared 101 PLF patients with 101 TLIF patients [37]. While the authors demonstrated greater improvement in ODI and Short-Form-6D (SF-6D) at 12 months in the TLIF population, it was at the high cost of an additional $4830.…”
Section: Interbody Fusionmentioning
confidence: 99%